IN VITRO EFFICACY EVALUATION OF PROBIOTIC PROPERTIES OF BACILLUS ALBUS STRAIN PLAFFS01 - D. Raghu; M. Parthasarathy; J. Ramesh; G. Sarathchandra (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Bacillus albus strain PLAFFS01 was screened for in vitro probiotic properties including thermal tolerance, simulated gastrointestinal fluids resistance, hydrophobicity of bacterial surface, autoaggregation, adhesion capacity, antioxidative activity and antibiotic sensitivity. Bacillus albus strain PLAFFS01 was identified by amplifying 1514 bp of 16S rRNA ribosomal gene sequence and the sequence was deposited in the NCBI GenBank database with accession number PP968101. Results showed that the Bacillus albus strain PLAFFS01 was found high survival rate of 97.72% and 79.09% in simulated gastric and intestinal fluids respectively. Also it exhibited sensitivity to antibiotics and good performance on hydrophobicity (64.88%), autoaggregation (41.75%), DPPH free radical scavenging activity (92.68%) and adhesion ability to HT-29 intestinal epithelial cell lines. Moreover, this strain possessed considerable tolerance to thermal treatment, which shows that it can be used in the feed industry also. In conclusion, the present study demonstrated that Bacillus albus strain PLAFFS01 is a potential probiotic candidate.